(untitled) (Architecture Image Studies, 2025)
Therapeutic photography is generally better known by the realism photography style that displays photos as they are as a medium to store memories, but in this research the author tries to take a different approach through a pictorial photography style that emphasizes the concept in the photo. The purpose of this research is to find out how therapeutic photography with a pictorial style approach can still provide therapeutic benefits as perceived in the realism style approach? Then how is the therapeutic effect produced by the photo fifteen years later since the photo was first made? This research uses a qualitative methodology, with a case study approach for an exploratory, longitudinal analysis of the fifteen-year experience of the subject named Evita Sugiarto. In addition, the researcher also wanted to further explore Roland Barthes’ Studium and Punctum theories on the subject. The research results are that conceptual photography can still provide therapeutic benefits to Evita Sugiarto even for fifteen years through the Studium and Punctum of her photo.